The role of heterotopy and heterochrony during morphological diversification of otocephalan epibranchial organs. Issue 3 (16th June 2022) - Cohen, Karly E.; Ackles, Acacia L.; Hernandez, L. Patricia
Abstract: Epibranchial organs (EBOs), found in at least five of the eight otomorphan families, are used to aggregate small prey inside the buccopharyngeal cavity and range in morphological complexity from a singular, small slit on the pharyngeal roof to several, elongated soft tissue tubes. Despite broad phylogenetic representation, little is known about the origin, development, or evolution of EBOs. We hypothesize that both heterochronic and heterotopic changes throughout the evolution of EBOs are at the root of their morphological diversity. Heterochrony is a foundational explanation in developmental studies, however, heterotopy, a developmental change in spatial or topographical relationships, can have even more profound effects on a given structure but has received relatively little attention. Here, we investigate how developmental mechanisms may drive morphological diversity of EBOs within otomorphan fishes. We compare early pharyngeal development in three species, Anchoa mitchilli (Engraulidae) which has the most basic EBO, B. tyrannus (Clupeidae) which has a more complex EBO, and Hypophthalmichthys molitrix (Cyprinidae) which has the most complex EBO yet described. Using branchial arch growth rates and morphological analyses, we illustrate how both heterochronic and heterotopic mechanisms are responsible for some of the phenotypic diversity seen in otomorphan EBOs. Importantly, we also identify conserved developmental patterns that further our understanding of how EBOs may have first originated and evolved across actinopterygian fishes. Abstract : The epibranchial organ (EBO) is a novel feeding structure in several Otomorphan fishes and thought to allow for the efficient aggregation of small prey. EBOs are morphologically diverse ranging from a single, muscular opening to elongated soft tissue tubes. Despite broad phylogenetic representation, little is known about the origin, development, or evolution of EBOs. Using branchial arch growth rates and morphological analyses, we illustrate how both heterochronic and heterotopic mechanisms are responsible for some of EBO phenotypic diversity. We also identify conserved developmental patterns that further our understanding of how EBOs may have first originated and evolved across actinopterygian fishes. Highlights: This manuscript details the development, origin, and evolution of epibranchial organs (EBOs) in three species of Otomorphan fishes: Anchoa mitchilli, Brevoortia tyrannus, and Hypophthalmichthys molitrix . Through a comparative analysis, we find evidence that both heterochronic and heterotopic mechanisms are responsible for the morphological diversity of EBOs and that a heterotopic shift is likely what allowed this organ in silver carp to be so much more complex than those seen in other fishes.